PSYCHOPHYSIOLOGICAL APPROACHES IN TEACHING STUDENTS OF DENTAL FACULTIES - N. P. Makhlynets (Український стоматологічний альманах)
The article contains materials of pilot study, which is devoted to the formation of directed practical knowledge and skills in students. When using the classic system of students’ training for practical knowledge and skills in periodontology teacher spends a lot of time, but observes poor mastering the material through students` misunderstanding of what their tasks are.